On the cation uptake mechanism of Sphagnum mosses - Viljo Puustjärvi (Agricultural and Food Science, 1959)
In the present investigation the cation uptake mechanism of Sphagnum mosses has been dealt with and a theory relating to it has been developed. In brief, the theory is as follows. In the points of growth of the Sphagnum mosses colloidal acids saturated with hydrogen ions, so-called acidoids, are continuosly formed. They produce an electrical potential difference between the moss and its growth base. The potential difference with reference to the growth base increases from the boundary surfaces between moss and peat towards the points of growth. This potential difference forces the base cations to pass over from the peat into the moss plant in the direction of the potential and at a rate controlled by it. In the investigation this potential difference has been determined experimentally with the aid of NERNST’s formula.